2007
DOI: 10.1038/sj.onc.1210258
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 promotes anchorage-independent growth by transcriptional repression of IGFBP-3

Abstract: CDX2 is a Drosophila caudal-related homeobox transcription factor that is important for the establishment and maintenance of intestinal epithelial cells. We have reported that CDX2 promotes tumorigenicity in a subset of human colorectal cancer cell lines. Here, we present evidence that CDX2 negatively regulates the welldocumented growth inhibitor insulin-like growth factor binding protein-3 (IGFBP-3). Specifically, CDX2 binds to the IGFBP-3 gene promoter and can repress IGFBP-3 transcription, protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Our results are consistent with previous published data for metastasis models of other tissues: in a prostate cancer model, using the transgenic PB-HiMyc mice crossed with an IGFBP-3 knockout mouse model [28] showed that the absence of IGFBP-3 increased metastasis to distant organs. In other in vitro models, IG-FBP-3 inhibited migration of endometrial cancer cells [32] and was involved in inhibiting anchorage-independent growth [33], which could favor a metastatic process.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with previous published data for metastasis models of other tissues: in a prostate cancer model, using the transgenic PB-HiMyc mice crossed with an IGFBP-3 knockout mouse model [28] showed that the absence of IGFBP-3 increased metastasis to distant organs. In other in vitro models, IG-FBP-3 inhibited migration of endometrial cancer cells [32] and was involved in inhibiting anchorage-independent growth [33], which could favor a metastatic process.…”
Section: Resultsmentioning
confidence: 99%
“…The role of CDX2 is probably also ambiguous in this matter, and may differ according to conditions. Two cancer cell line studies indicate that CDX2 under anchorage-independent growth conditions (resembling spreading cells) promotes proliferation and increases resistance to programmed cell death [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…CDX2, a Drosophila caudal-related homeobox transcription factor has been reported to promote tumorigenicity in a subset of human colorectal cancer cell lines (155). CDX2 also negatively regulates IGFBP-3 by specifically binding to the IGFBP-3 gene promoter and repressing IGFBP-3 transcription, protein expression, and secretion (155).…”
Section: Factors That Influence the Suppression Ormentioning
confidence: 99%